G20 rising powers' status seeking through social creativity: The case of South-South development cooperation - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This study aims to explore how rising powers who are also donors within the G20 strive to achieve a positively distinctive identity in the field of development cooperation through status-seeking strategies. The article employs Social Identity Theory (SIT) to critically examine and understand the increasing importance of South-South cooperation in the foreign policies of the nine selected G20 rising donors (namely China, Russia, Brazil, Indonesia, South Africa, Turkey, Mexico, India and Argentina). For this purpose, it will first explain why status matters for rising powers. Second, it will present the linkage between status-seeking policies of states and state identity. Third, it exposes social creativity as a driver of state behaviour. And fourth, it focuses on G20 rising powers' quest for status through social creativity with a particular focus on South-South development cooperation.
Keywords: G20; rising powers; status; Social Identity Theory; south-south cooperation; development cooperation; DISADVANTAGED GROUP; ACCEPTANCE; RESPONSES; BRAZIL